Geochemistry and zircon U–Pb ages of early Ordovician syenites from the Inexpressible Island, Antarctica and tectonic implications - Gao, Peng; Tang, Limei; Chen, Ling (Frontiers in Earth Science, 2023)
The Ross Orogenic Belt is in the Antarctica Transantarctic Mountains. North Victoria Land Granite Harbour Intrusive com-plex (GHI) record the tectonic-magmatism evolution of Ross orogeny. Extensively developed post-collisional granites around this margin of early Paleozoic magmatism can provide insights into the growth of continental crust through accre-tionary orogenesis. We provide geochemical and geochronological data from syenites from the Terra Nova Bay, north Vic-toria Land in order to constrain its tectonic evolution and setting. The syenite belongs to the potassium-alkaline, calc-alkaline series and are characterized by high concentrations of rare earth elements (REE) and large ion lithophile elements (LILE), and low content in high field strength elements (Nb, Ta, P, Ti). The petrographic and geochemical signatures show a possible island-arc granite affinity. LA-ICP-MS zircon U-Pb dating results suggest that the Inexpressible Island syenite were emplaced at ca. 471.8±1.8 Ma and 477.3±1.7 Ma, respectively. Zircon εHf(t) values range from −7.4 to −9.1; average −8.2 and whole-rock εNd (t) values range of −8.5 to −10.3, indicating that formed by the partial melting of the lithospheric mantle enriched with subduction slab fluids and subcontinental lithosphere. Whereas, the syenite has strong positive Eu anomaly and a positive Sr anomaly, suggesting that plagioclase cumulate crystallization occurred in the magma source area. Furthermore, through integration with previous studies, we suggest that syenite is as a result of melting zone of an older previously subduction enriched layer of the subcontinental lithospheric mantle (SCLM). To enable syenite emplacement we suggest a tectono-magmatic model that invokes alternating phases of extension and contraction in the overriding plate. Finally, we report the youngest age of (post-orogenic) magmatism occurred during extension in the overriding plate ca. 478–471 Ma.